ALTERNATIF TINDAKAN MENINGKATKAN PENDAPATAN PETANI KOPI RAKYAT KABUPATEN JEMBER - Purnamie Titisari (UNEJ e-Proceeding)
This study aims to identify the internal factors (strengths and weaknesses) and external factors (opportunities and threats) agribusiness coffee in Jember district and to formulate action plan (plan of action) on each value factors to increase the income of coffee farmers folk seed. This study will use three approaches to collecting data, namely participant observation, semi-structured interviews and focus group discussions. The analytical method used is the SWOT analysis. The research result obtained is the process of obtaining seed until the sale has not done a system of partnerships that benefit farmers but actually beneficial owners of capital. There are limitations to the ability of human resources, facilities and technology to farmers as well as the supply of capital is still limited, and only assisted by a cooperative that level of progress is still lacking due to limited funds cooperative management. The results of further research, programs to increase the production and quality of sustainable coffee plants. Needed gathering coffee development strategy through the revitalization of land, seed, infrastructure and facilities, improvement of human resources, financing farmers, institutional and industrial technology downstream farmers.